Mauritius : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix discusses initial performance and other issues relating to the implementation of the value-added tax in Mauritius in 1998. The paper highlights that as the Mauritius economy has continued to expand at a relatively rapid pace, the need for the monetary authorities to enhance their ability to influence domestic liquidity, as well as to ensure the integrity of the banking system, has become increasingly apparent. The paper also analyzes various issues in the banking sector of Mauritius.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet